The Influence Of Auditor Competence, Independence, And Professionalism On Audit Quality At Public Accounting Firms In Medan - Simarsoit, Fany Anatasya; Sucipto, Tia Novira (Journal of Management, Economic, and Accounting, 2025)
This study aims to examine the influence of auditor competence, independence, and professionalism on audit quality in Public Accounting Firms (PAF) in Medan. Data were collected through questionnaires distributed to auditors working in various PAFs in the city. The analytical method used is multiple linear regression with the assistance of SPSS software. The results indicate that competence, independence, and professionalism have a positive and significant effect on audit quality, both partially and simultaneously. These findings suggest that auditors with high competence, strong independence, and a high level of professionalism tend to produce higher-quality audits. This study contributes to strengthening audit practices in public accounting firms and serves as a consideration in developing training programs and internal policies. Furthermore, it can be a useful reference for future academic research in the field of auditing and accounting.